Aplikasi Disain Komposit Pusat Pada Proses Pengecatan Mobil Bekas - Abeth Novria Sonjaya; Kevin Hervito; Tri Atmoko (Jurnal Teknologi, 2021)
The business of buying and selling used cars is increasingly substantial in Indonesia, in the era of globalization progressively developing depends on demands a process that must be fast, precise, and economical. Repair to body, chassis, and engine are competency expertise in the field of Automotive Engineering that emphasizes automotive repair service skills.  at now selling price of used cars, it is necessary to do repairs, the process of repairing used cars or better known as refurbishment work pre-owned cars is mostly done by small-scale used car buying and selling businesses. In order for used cars to return to their like-new condition, generally small-scale used car sellers carry out the process of repairing the vehicle themselves, especially repairs to the vehicle's body paint. This study aims to process of painting a Toyota Avanza car bodypaint against the thickness of the paint using a spray booth tool by using the model of central composite design (CCD). The effect of spray-on booth temperature, interstice size of the spray gun, and time according to the thickness of the paint will be analyzed using the CCD method. This spray booth painting technology is expected to help reduce bodypaint lead time. The results of the ANOVA (Analysis of Variance) regression analysis, the temperature of the spray booth, interstice size of the spray gun, and time are the factors that most significantly affect the thickness of the paint. The operating conditions to produce optimal paint thickness are temperature 55oC, interstice size of spray gun of 1.7 mm and time of painting and drying of 30 minutes, the resulted of a thickness of the paint for used and new cars are 130.2 μm and 81.84 μm., with a coefficient of determination for used and new cars of 90.78% and 96.19%.